TYPOLOGY OF ISLAMIC EDUCATION NEO-SALAFI VERSUS OF PROGRESSIVE ISLAM - Najwan Saada (Jurnal Pendidikan Islam, 2020)
AbstractThis article discusses the principles of two traditions of contemporary religious understanding in Islam today. Neo-Salafi and Progressive Islam, where these two groups are in contradiction with ideological principles, religious practice, and orientation. This article analyzes how these two groups develop a typology of Islamic religious education at the system level and the learning process. Some of the indicators studied to explain typology are tarbiyya and ta’dīb which are in the critical and non-critical ta’līm continuum positions in Islamic religious education. By using the descriptive reflective method, the identifier’s purpose of this typology is to provide theoretical contributions to academics and practitioners as material for reflecting on the pedagogical method of Islamic education in the contemporary era.